NEW PLANETARY NEBULAE - PEIMBERT, M; BATIZ, G (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1954)
Ten new planetary nebulae were found after an examination of the Tonantzintla objective prism plates.
BOL OBS TONAN TACUB
Keywords: NEW, PLANETARY, NEBULAE; ASTRONOMIA Y ASTROFISICA; PLANETOLOGIA; GEOLOGIA PLANETARIA